Welcome to IMIA (Yearbook of Medical Informatics, 2020)
BOARDPresidentSabine Koch, Sweden (2019 - 2021)President electJack Li, Taiwan (2019 - 2021)Past PresidentChris Lehmann, United States (2019 - 2021)SecretaryDr. Petter Hurlen, Norway (2015 - 2021)TreasurerJohanna Westbrook, Australia (2017 - 2020)Vice PresidentsMedInfoNajeeb Al-Shorbaji, Jordon (2020 - 2021)MembershipDr. Daniel Luna, Argentina (2018 - 2021)ServicesDr. Brigitte Séroussi, France (2016 - 2019)Special AffairsJennifer Bichel-Findlay, Australia (2019 - 2022)Working & Special Interest GroupsLuis Fernandez Luque (2019- 2022)CEOElaine Huesing, CanadaIMIA Web site:www.imia.orgRegional Vice Presidents to IMIAAPAMI: Asia Pacific Association for Medical InformaticsVajira Dissanayake, Sri LankaEFMI: European Federation for Medical InformaticsChristian Lovis, SwitzerlandHELINA: Pan African Health Informatics AssociationGhislain Kouematchoua Tchuitcheu, Germany/CameroonIMIA-LAC: Health Informatics Association for Latin America and the CaribbeanMarcelo Lucio da Silva, BrazilMENAHIA: Middle East and North African Health Informatics AssociationRiyad Al Shammari, Saudi ArabiaNorth American RegionJames Cimino, United StatesIMIA Liaison Officers, ex officioWHO Liaison OfficerPatrick Weber, SwitzerlandIFIP Liaison OfficerHiroshi Takeda, JapanISO Liaison OfficerMichio Kimura, Japan